G337(P) Renal angioplasty in patients with alagille syndrome and renovascular hypertension: is it safe and does it work?. (25th October 2020) - Rubens, M; Kurt-Sukur, ED; Patel, P; Roebuck, D; Marks, S; Tullus, K; Stojanovic, J
Abstract : Introduction: Whilst renal involvement in Alagille syndrome is common, its manifestation is varied, and bilateral renal artery stenosis is relatively rare. Patients with Alagille syndrome are at increased risk of bleeding and this must be taken into account when planning invasive procedures such as percutaneous transluminal angioplasty (PTA). We reviewed four cases of children with Alagille syndrome and renal artery stenosis who were referred to the renovascular service at a large tertiary paediatric nephrology centre for management of hypertension. We aimed to determine whether PTA was safe and effective for the treatment of renovascular hypertension in such patients. Methods: A retrospective search was conducted of a local database of all patients with confirmed Alagille syndrome and renovascular hypertension treated with PTA. Data for each patient was then collected from medical and electronic records. Results: Four patients were identified with Alagille syndrome and renovascular hypertension. In total, 8 PTA procedures were carried out including one for management of renal artery aneurysm. There were no intra or peri-operative complications including significant bleeding. In addition, two patients needed unilateral nephrectomies for non-functioning kidneys. 75% of patients had improvement in blood pressure at last follow up. There was a peri-procedural rise in serum creatinine of 10–73% in 57% of PTA procedures, the majority of which normalised at last follow up. Conclusions: In a tertiary paediatric renovascular centre, PTA can be safely performed in patients with Alagille syndrome. Improvement in blood pressure was observed in 75% of cases. Furthermore, this study confirms that patients with Alagille syndrome and renovascular hypertension might need more than one PTA and these should be done in a specialist centre with experience in this patient cohort.